Play with Trigonometry

Geometry Level 3

Let the value of the given expression N = 0 cos N θ 3 N \sum _{ N=0 }^{ \infty }{ \frac { \cos { N\theta } }{ { 3 }^{ N } } } = S then value of S to three decimal places is: Where cos θ \cos { \theta } = 1 3 \frac{1}{3} and θ ϵ ( 0 , π 2 ) \theta \quad \epsilon \quad \left( 0,\frac { \pi }{ 2 } \right)

Inspiration: Lucas Chaves Meyles


The answer is 1.000.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

First of all, great problem! I am going to take Chew-Seong Cheong's approach. S = N = 0 cos N θ 3 N = 1 2 ( N = 0 ( e i θ 3 ) N + N = 0 ( e i θ 3 ) N ) = 1 2 ( 1 1 1 3 e i θ + 1 1 1 3 e i θ ) = 3 6 2 e i θ + 3 6 2 e i θ = 36 6 ( e i θ + e i θ ) 40 12 ( e i θ + e i θ ) = 9 3 cos θ 10 6 cos θ = 9 3 ( 1 3 ) 10 6 ( 1 3 ) = 8 8 = 1.000 \begin{aligned} S & = \sum_{N=0}^\infty \frac{\cos N\theta}{3^{N}} \\ & = \frac{1}{2}\bigg(\sum_{N=0}^\infty \bigg(\frac{e^{i\theta}}{3}\bigg)^{N} + \sum_{N=0}^\infty \bigg(\frac{e^{-i\theta}}{3}\bigg)^{N}\bigg) \\ & = \frac{1}{2} \bigg(\frac{1}{1-\frac{1}{3}e^{i\theta}} + \frac{1}{1- \frac{1}{3} e^{-i\theta}} \bigg) \\ & = \frac{3}{6-2e^{i\theta}} + \frac{3}{6-2 e^{-i\theta}} \\ & = \frac{36 - 6(e^{i\theta} + e^{-i\theta})}{40 - 12(e^{i\theta} + e^{-i\theta})} \\ & = \frac{9 - 3\cos \theta}{10 - 6\cos\theta} \\ & = \frac{9 - 3(\frac{1}{3})}{10 - 6(\frac{1}{3})} \\ & = \frac{8}{8} \\ & = \boxed{1.000} \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...